Interpretações socioambientais da mística do movimento dos trabalhadores rurais sem terra - Carvalho, Andréa Freire de (2013)
This dissertation aims to unveil in which extension the Mystic of the Rural Landless Workers Movement (MST) contributes to the formation of those involved in the Movement in relation to the environment. In this way, we investigated how the mystic was used in formal and informal spaces, and, which elements from the environment were used in the pedagogical practices developed in the classroom´s settlement as well as in the MST´s training courses. The methodology used was based on descriptive phenomenology, aiming to comprehend the meaning that this mystic has to the teachers of the settlements of Sergipe State, as well as to describe the procedures used in the mystics´ elaboration produced by the rural workers settled as well as their interation with the formation of the men concerning the environment. Therefore, we conclude that the mystic of MST constitutes itself as an important element in the formation of the rural workers in relation to socioenvironmental affairs. Furthermore its contentes cover since the occupation of the land, being imbued by the preservation/conservation of headwaters of rivers up to the care that must be taken when using pesticiles, as well as the correct way of disposing the different kinds of waste, and also claiming the human rights among others possibilities, in which the mystic has contributes to the collective formation in socioenvironmental area, cultural area, educational and economic area as a way of contribute effectively to the formative process of the settlers.